Sequence liquid manipulation on a multifunctional snowflake-patterned interface with dual unidirectional wettability. Issue 16 (4th April 2023) - Wu, Weiming; Bai, Haoyu; Yang, Yi; Li, Guoqiang; Chen, Zuqiao; Tang, Chengning; Yin, Huan; Lai, Lin; Liu, Jiasong; Xuan, Sensen; Song, Yuegan; Liu, Senyun; et al.
Abstract : Inspired by the fractal structure of snowflake and the Janus interface of lotus leaf, here we present a sequence liquid transporting interface with a dual unidirectional pathway for manipulating micro-droplets in fog collection and microreactions. Abstract : The spontaneous directional transport of liquid droplets on specific bionic functional structures shows great potential for applications in water harvesting, chemical microreactions, biomedical analysis, etc. Although current research has achieved directional droplet transport of asymmetric structure, efficient and adaptable continuous droplet transport in complex environments remains challenging. Herein, through the fusion of inspiration from the fractal structure of snowflakes, the geometric gradient of a cactus spine, and the wettability contrast of a perforated lotus leaf, we propose a multifunctional snowflake-patterned interface (MSPI) for sequence droplet manipulation. Due to the synergistic effect of the dual asymmetry mechanism, the MSPI can propel droplet directional transportation with a dual unidirectional pathway, i.e., on-surface transport from the tip to the root and penetration transport from the confined-superhydrophilic pattern to the unconfined-superhydrophilic surface. In particular, a novel application of the MSPI was creatively designed to realize a specific chemical reaction between two kinds of microdroplets and complete solid–liquid separation. In addition, the structural advantages of the MSPI have also been proven to have an excellent fog collection effect with localized liquid discharge, which can be targeted to supply water to plants in a foggy environment. This work opens an avenue for a multi-mechanism coordination strategy based on biomimetic structures and thus should provide a valuable platform for developing chemical microreactors and water extraction from fog for irrigation.